A NEW SIZE RECORD OF HILSA, TENUALOSA ILISHA (HAM., 1822) FROM HOOGHLY ESTUARY, WEST BENGAL - SANDHYA, K. M.; M., SAJINA A.; SURESH, V. R.; MANNA, R. K.; BEHERA, B. K.; MUKHERJEE, J.; BANIK, S. K.; KAR, S.; MUKHOPADHYAY, M. K. (Journal of the Inland Fisheries Society of India, 2021)
The Hilsa shad, Tenualosa ilisha (Hamilton, 1822), occurs in foreshore areas, estuaries, brackish-water lakes and freshwater rivers of the western division of the Indo-Pacific region. It is well known as a delicious, high priced fish of commercial and cultural importance, especially in state of West Bengal and the North Eastern states of India as well as Bangladesh. Along the Indian coast of Bay of Bengal, the Hooghly estuarine system is one of the largest and most productive estuaries and is an important migratory route of the anadromous hilsa. The estuarine system is constituted by the first offshoot of river Gangathe Bhagirathi, which flows southwards through the lower Ganga deltaic plains and joins Bay of Bengal in Sunderbans. Hilsa shad is the most economically significant fishery of the system and it is a major contributor to the total fish landings of this system. Hydrological alterations in the form of barrages and dams built across the major east and west coast rivers, especially along the Ganges and Narmada have blocked its migratory routes to breeding grounds in riverine areas, resulting in the collapse of its fishery in the river stretches above these barrages and as a result, hilsa landing is now concentrated in estuarine part of these rivers (Raja, 1985; De, 1998). After commissioning of the Farakka barrage in 1975, the hilsa fishery is confined to downstream of the barrage, the Hooghly-Bhagirathi system. The indiscriminate exploitation of hilsa adults as well as juveniles during the past years has caused the decline of the once lucrative commercial fisheries of the fish, more particularly along the Hooghly estuary, due to recruitment failure. The comparison of time scale mean size recorded from Hooghly-Bhagirathi river system over past years indicated a declining trend and an increasing contribution of smaller size groups in the catch pointing towards the growth overfishing of hilsa populations. The aim of this paper represents a new record size of hilsa with record fecundity from Hooghly estuarine system